(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the distinctive features of the belles-lettres style in English and Uzbek, focusing on its universal applicability and unique linguistic characteristics. Unlike other functional styles, the belles-lettres style encompasses all aspects of human activity and life, serving as a medium to reflect emotions, inner worlds, and social realities. It aims to evoke aesthetic and emotional responses in readers through artistic use of language. The study identifies key functions of this style, including informative, persuasive, cognitive, and aesthetic roles, and explores its manifestation in prose, poetry, and drama. Comparative analysis reveals the use of diverse linguistic units in both languages, such as colloquial expressions, literary terms, and stylistic devices, which serve the artistic-aesthetic purpose. While English categorizes the style into poetic, prosaic, and dramatic speech, Uzbek literature offers similar classifications with additional cultural nuances. In particular, it is divided into two - the language of prosaic and poetic works. This research highlights how belles-lettres style bridges cognitive and aesthetic processes, enriching the literary experience.